Manajemen Kinerja Kepemimpinan Dalam Mengelola Konflik Organisasi - A, Aswaruddin; Mtd, Nadya Putri; Ramadhani, Desmawati; Sitompul, Uswatun Hasanah; Sagala, Chairunnisa (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This article discusses how a leader's performance or performance management works in dealing with existing conflicts by carrying out conflict management well so that the management of an organization or institution led can be managed well. The aim of this research is to find out how a leader manages conflict within a company or organization. This research uses qualitative research methods, namely basic research and uses literature study by reviewing previous research in the form of books and other research articles. The results of this research reveal several things that a leader must do when facing conflict, especially in terms of communication, the role and skills of a leader in the organization so that the leader's performance in leadership in dealing with existing conflicts will be carried out effectively and efficiently.